MU'JAM AROBY KITAB AL AROBIYAH BAINA YADAIK - Ma'arif, A Syamsul (Universitas Ahmad Dahlan)
A dictionary is one of the supporting elements in language learning. The dictionary helps language learners to find the correct meaning. Mu’jam Aroby Kitab Al Arobiyah Baina Yadaik is one of the dictionaries in Arabic Learning. The purpose of this paper is to thoroughly explore the Mu’jam Aroby Kitab Al Arobiyah Baina Yadaik in the use the book of Al Arobiyah Baina Yadaik. In this paper a brief history of the writer of the dictionary and the advantages and disadvantages of this dictionary.